2014
DOI: 10.1371/journal.pone.0087465
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Endovascular vs. Open Surgery Repair for Ruptured Abdominal Aortic Aneurysms: A Meta-Analysis

Abstract: ObjectivesTo systematically review studies comparing peri-operative mortality and length of hospital stay in patients with ruptured abdominal aortic aneurysms (rAAAs) who underwent endovascular aneurysm repair (EVAR) to patients who underwent open surgical repair (OSR).MethodsThe Medline, Cochrane, EMBASE, and Google Scholar databases were searched until Apr 30, 2013 using keywords such as abdominal aortic aneurysm, emergent, emergency, rupture, leaking, acute, endovascular, stent, graft, and endoscopic. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
(56 reference statements)
1
17
0
3
Order By: Relevance
“…In a previous study, the mean hospital length of stay was 7 days after EVAR treatment of rAAAs [22]. Similar to that study, the mean hospital stay in the present study was 6.7 ± 3.5 days in the patients with a normal anatomy and 10.4 ± 15.5 days in patients with a hostile anatomy.…”
Section: Discussionsupporting
confidence: 89%
“…In a previous study, the mean hospital length of stay was 7 days after EVAR treatment of rAAAs [22]. Similar to that study, the mean hospital stay in the present study was 6.7 ± 3.5 days in the patients with a normal anatomy and 10.4 ± 15.5 days in patients with a hostile anatomy.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, rapid aneurysm growth with more than 10 mm per year represents another indication for early repair ( 4 ). In conclusion, these recommendations aim to prevent AAA rupture, a life-threatening event with mortality rates of approximately 65–85% ( 100 ).…”
Section: Treatment Indicationsmentioning
confidence: 99%
“…Since a metaanalysis by van Beek et al [87] showed that EVAR for rAAA repair is not inferior to OR in terms of short-term survival, it can therefore be recommended to use the same accustomed technique for rAAA as for the intact AAA. In the long term this means a further increase in EVAR for rAAA, especially since an additional literature meta-analysis including large retrospective multicenter studies, clearly favored the endovascular approach for rAAA with respect to in-hospital mortality [88].…”
Section: Treatment Of the Raaamentioning
confidence: 99%